EKC2010 proceedings of the EU-Korea conference on science and technology - Han, Man-Wook; Lee, Jehyun (Springer proceedings in physics, 2011)
Current research fields in science and technology were presented and discussed at the EKC2009, informing about the interests and directions of the scientists and engineers in EU countries and Korea. The Conference has emerged from the idea of bringing together EU and Korea to get to know each other better, especially in fields of science and technology.